Malthus in the bedroom: Birth spacing as a preventive check mechanism in pre-modern England - Francesco Cinnirella; Marc P. B. Klemp; Jacob L. Weisdorf (Center for Economic Studies and ifo Institute (CESifo), 2012)
We question the received wisdom that birth limitation was absent among historical populations before the fertility transition of the late nineteenth-century. Using duration and panel models on family-level data, we find a causal, negative short-run effect of living standards on birth spacing in the three centuries preceding England's fertility transition. While the effect could be driven by biology in the case of the poor, a significant effect among the rich suggests that spacing worked as a control mechanism in pre-modern England. Our findings support the Malthusian preventive check hypothesis and rationalize England's historical leadership as a low population-pressure, high-wage economy.
Keywords: J11; J13; N33; 330; spacing; birth intervals; fertility; limitation; natural fertility; preventive check; Familienplanung; Fruchtbarkeit; Lebensstandard; Sozialgeschichte; Großbritannien